The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1179/1743294413y.0000000161
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sealing on corrosion behaviour of plasma-sprayed Cr2O3–8TiO2 coating

Abstract: Plasma-sprayed Cr 2 O 3 -8 wt-% TiO 2 coatings were deposited on mild steel and sealed by epoxy resin and silicone resin in different processes. The microstructure and corrosion resistance of all coatings were investigated. The results showed that silicone resin sealant can seal the coating well and 91% of interconnected porosity was blocked. The sealant can penetrate into the coating by more than 280 mm. The coating sealed with silicone resin in vacuum conditions had the highest corrosion potential E corr (23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 21 publications
2
13
0
1
Order By: Relevance
“…Previous studies on thermal spray coatings showed that the immersion time may have a significant effect on corrosion performance of thermally sprayed coatings. [14][15][16][17][18] Conclusion Based on the results from the above experiments, the following conclusions can be drawn. 1.…”
Section: Microhardness Measurements and Polarisation Studymentioning
confidence: 77%
“…Previous studies on thermal spray coatings showed that the immersion time may have a significant effect on corrosion performance of thermally sprayed coatings. [14][15][16][17][18] Conclusion Based on the results from the above experiments, the following conclusions can be drawn. 1.…”
Section: Microhardness Measurements and Polarisation Studymentioning
confidence: 77%
“…% NaCl solution. Unfortunately, there are certain micro-pores and micro-cracks in the assprayed ceramic coating due to the characteristic of the formation of the coating [17,18,26]. Some of the open pores and cracks will act as the tunnel for the corrosion medium to penetrate the coating to corrode the substrate.…”
Section: Discussionmentioning
confidence: 99%
“…Oxide ceramics, due to their excellent properties including high hardness, high chemical inertness [13,14] in a variety of aggressive environments [15], and good wear resistance, are promising candidates as corrosion-resistant coatings in industrial applications, although there are some inevitable defects in the coatings [16,17]. Generally, the defects come from unmelted particles, inadequate flow or fragmentation of molten particles under impact status, shadowing effects caused by an improper spraying angle, and entrapped gas [18]. Moreover, vertical and horizontal cracks or pores may occur due to the high cooling rate of the individual splats and poor inter-lamellar bonding [19].…”
Section: Introductionmentioning
confidence: 99%
“…Sol-Gel procedure for preparing KH570-SiO 2 hybrid agent. Only connecting pores and/or micro-cracks from coating surface to substrate serve as transmitting channels of corrosion medium, so iron reagent test was considered to evaluate the porosity of 'connecting pores and or micro-cracks' of the coatings [7,15]. And the procedure is in accordance with the Chinese standard of the porosity test method for thermal spray coating (JB/T 7509-94), HITACHI-S3400N Scanning Electronic Microscopy (SEM) and Hirox KH-7700 Stereomicroscope (SM) were used to observe microstructure and eroded surface morphology of the coating.…”
Section: Apparatuses and Methods Of Analysismentioning
confidence: 99%
“…Sealing treatment is deemed as an efficient and attractive method on overcoming the disadvantage of plasma spray coating (PSC) mentioned above [5][6][7][8]. In general, there are two sorts of sealing materials [7,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%